Peningkatan Ketahanan Pangan Lokal Melalui Penerapan Cara Produksi Pangan Olahan Yang Baik Pada Industri Kecil dan Menengah - Marendra, Fajar; Rosalina; Irawan, Candra; Utami, Andita; Putri, Imalia Dwi; Sutarni, Yayan Dwi (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Local food security is a strategic issue in supporting national food independence and community welfare. However, small and medium food enterprises (SMEs) often face challenges in applying quality production standards, particularly the principles of Good Processed Food Production Practices (CPPOB). This community engagement activity aims to enhance the knowledge and awareness of SME actors regarding the importance of CPPOB implementation to ensure food safety and quality. The program consisted of three stages: preparation, implementation, and evaluation. The counseling was conducted at the production site of IKM Aji Berkah, which produces cassava and banana chips, using interactive lectures and discussions. Evaluation results showed an increase in participants' average scores from 63.52 to 89.92 after the program. All participants (100%) met the Minimum Mastery Criteria, and the paired t-test indicated a statistically significant improvement (P < 0.01). This activity proves that CPPOB counseling effectively strengthens SME actors’ capacity to produce hygienic and safe food, while also contributing positively to the enhancement of local food security.